Analysis of student activeness in mathematics learning with Merdeka Curriculum - Maheswari, Gabriela Alvina; Saraswati, Endah; Pratini, Haniek Sri (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
The curriculum in Indonesia has gone through various changes which are expected to make education in Indonesia grow and educate the nation's children. Government developing a Merdeka Curriculum. The Merdeka Curriculum gives students the freedom to seek scientific information so that it fosters activeness in students in learning. The purpose of this research is to know and describe the steps to overcome students when learning mathematics. This Type of research is qualitative research using descriptive methods. This research was conducted at senior high school in Surakarta with the research subjects being students of class E4 at senior high school in Surakarta and having the research objective of knowing and describing things that make students active and inactive which make students during Mathematics Learning. Furthermore, the method of collecting data in this study is observation, interviews, and giving appointments to students. Analysis conducted by researchers namely data collection, analysis of data obtained, drawing conclusions. The results of this study are the activeness of students supported by the division of small groups to build student activity in the classroom. The enthusiasm of educators can build student activity such as giving games before learning takes place. Educators also deliver material in an interesting way to make students active to learn in the classroom.